EVALUASI ANALISIS GEOTEKNIK PADA TAMBANG TERBUKA BATUBARA PIT NORTH WEST PT ANAK TAMBANG INDONESIA JOB SITE PT ADIMITRA BARATAMA NUSANTARA, KALIMANTAN TIMUR - Parissing, Vinsentia; Hariyadi, Sundek; Saptono, Singgih; Dwinagara, Barlian (Indonesian Mining Professionals Journal, 2024)
On a mine slope there will be a driving force and a resisting force. The mine slope will collapse if the driving force is greater than the resisting force. Thus, the principle of mitigating mine slope failure is to reduce the driving force or increase the resisting force. PT Adimitra Baratama Nusantara intends to develop a new mining area in the North-West area within the IUP area. Therefore, it is necessary to carry out a geotechnical study that focuses on slope stability analysis to support open-pit coal mining plans based on data from geotechnical investigations in the field, secondary data and geotechnical laboratory test data. Geotechnical modeling for slope stability analysis was carried out using the Finite Element Method because the overburden and interburden sedimentary rocks of coal seams are considered to have behavior approaching elasto-plastic, so that it will provide results that are close to the actual situation in the field. Modeling and slope stability analysis of the mine opening design represented by section-01 and section-03 with the height of each opening being 126 m and 119 m shows that the high-wall and low-wall slope designs are not yet stable, so a re-design is necessary. with the mine opening floor simulated at level -110 and level -90.